Learning with self-generated drawings and the impact of learners’ emotional states - Navratil, Sabrina D.; Kühl, Tim (Frontiers in Psychology, 2023)
Introduction The present study examined the influence of emotional states when learning with self-generated drawings. It was assumed that learners in a positive emotional state would profit from learning with self-generated drawings, while learners in a negative emotional state would not profit from this strategy to the same extent but would rather benefit through reading. Methods University students (N = 123) were randomly assigned to one of four conditions resulting from a 2 × 2 design with self-generated drawings (yes vs. no) and emotional state (positive vs. negative) as independent variables. Results Results showed that learning with self-generated drawings was more beneficial for a following transfer test than learning without drawings – irrespective of a learner’s emotional state. The quality of self-generated drawings predicted the learning outcomes of the retention and pictorial test, but not for transfer. Discussion Missing effects of emotional states and the missing interaction with self-generated drawings will be discussed.